Ethnomedicinal plants in Chhattisgarh origin - Chandrakar, Kunal; Satapathy, Trilochan; Nayak, Manoj; Dhalendra, Ghanshyam; Kumar, Birendra (Creative Pharma Assent, 2014)
The survey on Ethano medicinal plant of Chhattisgarh origin has been carried out to gather information regarding potent medicinal plants and their uses. The survey report is focused on traditional practice ethnic natural resources for mitigation and cure from several ailments. Even today, these herbal medicines are in practice to cure variety of disease. The present investigation was conducted using questionnaire in rural areas situated around in Chhattisgarh. Traditional knowledge about plant wealth passes from generation to generation for conservation of the traditional medicine.